An alkyne hydrosilylation–Hiyama coupling approach to highly functionalised 1, 3-dienes. Issue 5 (26th March 2015) - McAdam, Catherine A.; McLaughlin, Mark G.; Cook, Matthew J.
Abstract : A high yielding and completely stereoselective hydrosilylation–Hiyama protocol has been established for the synthesis of highly functionalised E, E -dienes. Abstract : A high yielding and robust protocol for the stereodefined synthesis of 1, 3-dienes has been established through a hydrosilylation–Hiyama coupling strategy. In all cases the products were formed as single E, E isomers and conditions are tolerant of a wide range of functional groups not compatible with other methods.